UPACARA ADAT MANE’E PADA MASYARAKAT DESA KAKOROTAN DI KECAMATAN NANUSA KABUPATEN KEPULAUAN TALAUD - Hossiana Majhesty Priskilla Majampoh (Universitas Sam Ratulangi, 2023)
Traditional ceremonies are a form of local cultural identity of a traditional community that is considered to have values that are still quite relevant to the needs of the supporting community. The Mane'e traditional ceremony among the people of Kakorotan Village is part of the uniqueness of local culture, the Mane'e traditional ceremony has existed for a long time and has become part of people's lives. The traditional Mane'e ceremony is a traditional fishing activity using janur or called sammi. The traditional ceremony of Mane'e is held every year precisely in May, this traditional Mane'e ceremony has survived for a long time, generations since the 16th century which until now is still maintained and preserved its existence. Cultural values and local wisdom for the Kakorotan community generally contain knowledge systems, including that human abilities to remember what has been known are then conveyed to others. In addition, Mane'e is carried out in a series of marine E'ha wisdom systems in the strategy of fishing communities to preserve marine life for the survival of the Kakorotan community. The traditional ceremony of Mane'e begins with a prayer to God to ask for His grace to be given smoothness, safety and results during the implementation of the traditional Mane'e ceremony. The traditional Mane'e ceremony also begins with a period of abstinence or E'ha for one year both on land and at sea, the implementation of the traditional Mane'e ceremony begins with Maraca Pundagi (cutting the forest rope) and ends with Manarimma Alama (Thanksgiving). Keywords: Traditional ceremony, Mane'e, E'ha